Advertising Strategies In Malaysian Advertisements - Vasudevan, Chellammal (Universiti Sains Malaysia, 1983)
This research involves the study of strategies used by advertisers in their advertisements on television, newspapers, magazines in our country. Advertisements, as we know are part and parcel of our lives. We are exposed to advertisements everywhere we go, educating us about services and institutions, informing us about products and the benefits one can derive by using them.